Zanzibar night light : a lighting plan for UNESCO World Heritage Zanzibar Stone Town - Carlstén, Freija (SLU/Dept. of Urban and Rural Development, 2018)
Where? Zanzibar is considered to be the centre of Swahili culture, found all along the east coast of Africa. The main city, Stone Town, has for over a millennium constituted an important trading port, merging east African Bantu with Arab culture, adding elements from Persia, India and Europe (NE, 2017).